Chinese energy policy progress and challenges in the transition to low carbon development, 2006-2013 - Basso,Larissa (2014)
If the world is not to jeopardize the chances for human life on Earth, climate change must be mitigated; therefore, achieving low carbon development is crucial. China is the world's greatest GHG emitter, energy producer and energy consumer; investigating its energy-climate policy developments and international positions are of utmost importance to understand and tackle current stumbling blocks of the global energy and climate governance.